Analyses of the structure of wave functions and energies spectra of ground and low excited states of Ytterbium isotopes - Okhunov, Abduahim; Usmanov, Phazlitdin; Hassan, Torla; Abu El Sheikh, Mph’d Hk.M. (Elsevier, 2018)
Non – adiabatic effects in wave functions and energy spectra of ground (gr), beta_1, neta_2, gamma_1, gamma_2 and K^pi=1^+ rotational bands of 170;172;174Yb isotopes are studied, within the phenomenological model, which takes into account the mixing of ground beta_1, neta_2, gamma_1, gamma_2 and K^pi=1^+ rotational bands. The wave functions and energy of ground and low excited states are calculated. The finding reveals that the mixture of bands have been found to considerable impact on the wave functions of low – lying states of 0_m^+ and 2_l^+ bands.